Incredible rescue mission - Mian, Zanib (London: Hodder Children's Books, 2020)
When Omar and his friends come back after the school holidays, their lovely teacher seems to have been replaced by somebody much more grumpy. Overhearing other teachers talking about her, Omar decides something terrible has happened. Could she possibly have been abducted by ... aliens?! Omar persuades his friends to mount a rescue mission but what they find is very surprising!
Keywords: Children's stories